Follow-up of aphakic patients with anterior vitrectomy in one eye and uneventful cataract extraction in the fellow eye. Issue 11 (November 1978) - MacBeath, D.; David, R.
Abstract : Twenty patients had operations for bilateral cataract in 2 separate sessions, with uncomplicated extraction on one side and vitreous loss managed with anterior vitrectomy on the other. The cataracts, the type of surgery, and the postoperative treatment were identical in both eyes. The differences between the 2 eyes were not statistically significant so far as the amount of astigmatism, final visual acuity, and peripheral anterior synechiae were concerned. The main difference was found to be the period of time the vitrectomised eyes remained red and uncomfortable as compared to the eyes with uncomplicated surgery.